PERILAKU PETUGAS KESEHATAN TERHADAP PELAKSANAAN DALAM PEMBERIAN INISIASI MENYUSU DINI (IMD) PADA IBU YANG MELAHIRKAN SECARA NORMAL DI RSIA. BADRUL AINI KEL. TEGAL SARI III KEC. MEDAN AREA KOTA MEDAN TAHUN 2014 - Eka Yuni Ningsih; Lita Sri Andayani; alam Bakti Keloko (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Early breastfeeding initiation (early initation) is a series of activities where newborns instinctively perform activities that ends with finding the nipple of their mother soon breastfeeding from their mother’s nipple. The study aims to reveal the behavior of health workers towards the implementation of the provision of early initiation of breastfeeding in mothers who give birth normally in RSIA. Badrul Aini Kel. Tegal Sari III Kec. Medan Area Kota Medan on 2014. This is a descriptive study with a quantitative approach. The results were analyzed by descriptive quantitative depicted in percentage. The number of samples that interviewed were 34 people (total sample). The results showed all respondents are female which is 100%. Most of the respondents were aged 21-31 years that is 58.8%. Most of the education level of the respondents is D3 Midwifery that is 73.5%. And most of the respondents have worked for 1-5 years that is 50%. The knowledge of the health workers in good category is 70.6%. The attitude of the health workers in good category is 82.4% and the actions of the health workers in low category as many as 58.8%. Hope for the health worker improve the performance of the implementation of the provision of early initiation of breastfeeding (IMD) for the mother who give birth normally and provide the information for the mother and family about the benefits from early initiation of breastfeeding (IMD). Keywords: early breastfeeding initiation, behavior, health workers